2010
DOI: 10.1007/s10499-010-9342-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary lipid levels on growth performance, feed utilization and fatty acid composition of juvenile Japanese seabass (Lateolabrax japonicus) reared in seawater

Abstract: Triplicate groups of 40 Japanese seabass Lateolabrax japonicus (initial weight, 11.3 ± 0.4 g) reared in seawater (salinity, 30.0-33.0 g L -1 ) were fed with five isonitrogenous (41.3 ± 0.2% crude protein) and isoenergetic (18.5 ± 0.3 MJ kg -1 ) experimental diets formulated with increasing lipid levels (4.3, 8.4, 12.2, 15.8 and 20.1% lipid) for 10 weeks. Survival throughout the feeding experiment ranged from 87.5 to 100%, but the survival of fingerlings fed with the 4.3% lipid diet was significantly lower than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 20 publications
4
23
2
Order By: Relevance
“…Thus, a diet of 11.6% lipids was an optimal concentration for growth performance of juvenile gibel carp. These findings are consistent with previous reports on juvenile Japanese seabass ( Latelabrax japonicus ; Xu, Qin, Yan, Zhu & Luo ), tiger puffer (Kotaro, Takeshi, Nakahiro, Kazue & Tamo ), pike perch ( Sander iucioperca L.; Molna′r, Szabo′, Szabo′, Szabo′ & Hancz ) and juvenile GIFT tilapia ( Oreochromis niloticus ; Wang, Han, Feng, Yang, Guo, Wang & Xu ). In addition, we found that the WG in the high lipid group was the lowest, indicating that high dietary lipid levels have detrimental effects on juvenile gibel carp growth.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Thus, a diet of 11.6% lipids was an optimal concentration for growth performance of juvenile gibel carp. These findings are consistent with previous reports on juvenile Japanese seabass ( Latelabrax japonicus ; Xu, Qin, Yan, Zhu & Luo ), tiger puffer (Kotaro, Takeshi, Nakahiro, Kazue & Tamo ), pike perch ( Sander iucioperca L.; Molna′r, Szabo′, Szabo′, Szabo′ & Hancz ) and juvenile GIFT tilapia ( Oreochromis niloticus ; Wang, Han, Feng, Yang, Guo, Wang & Xu ). In addition, we found that the WG in the high lipid group was the lowest, indicating that high dietary lipid levels have detrimental effects on juvenile gibel carp growth.…”
Section: Discussionsupporting
confidence: 92%
“…), red drum ( Scienops oceelatus ; Ellis & Reich ), halibut ( Hippoglossus hippoglossus L.; Nortvedt & Tuene ) and Japanese seabass ( Lateolabrax japonicus ; Xu et al . ). The negative association between high dietary lipid levels and growth may be the result of lower feed intake (Tocher ; Xu et al .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Its occurrence and development are closely related to lipid metabolism key factors. It is well known that dietary lipid plays a key role in the growth of fish and the unreasonable lipid level could cause the physiological disorders of lipid metabolism (Xu, Qin, Yan, Zhu, & Luo, 2011), so we suspect that the unreasonable lipid level might lead to the massive fat deposition by regulating some key factors of lipid metabolism in fish body, especially in liver.…”
Section: Introductionmentioning
confidence: 98%